I suppose you mean
![g(x) = \frac x{2√(36-x^2)} + 18\sin^(-1)\left(\frac x6\right)](https://img.qammunity.org/2022/formulas/mathematics/college/vfgby39cz221sj01xyx1v03zoeumkudj3p.png)
Differentiate one term at a time.
Rewrite the first term as
![\frac x{2√(36-x^2)} = \frac12 x(36-x^2)^(-1/2)](https://img.qammunity.org/2022/formulas/mathematics/college/nu6dmqw7dze8945bxx2ag8jwssy06njaaa.png)
Then the product rule says
![\left(\frac12 x(36-x^2)^(-1/2)\right)' = \frac12 x' (36-x^2)^(-1/2) + \frac12 x \left((36-x^2)^(-1/2)\right)'](https://img.qammunity.org/2022/formulas/mathematics/college/cvgqgmzme2zgycks9j5g2etv393y1y86up.png)
Then with the power and chain rules,
![\left(\frac12 x(36-x^2)^(-1/2)\right)' = \frac12 (36-x^2)^(-1/2) + \frac12\left(-\frac12\right) x (36-x^2)^(-3/2)(36-x^2)' \\\\ \left(\frac12 x(36-x^2)^(-1/2)\right)' = \frac12 (36-x^2)^(-1/2) - \frac14 x (36-x^2)^(-3/2) (-2x) \\\\ \left(\frac12 x(36-x^2)^(-1/2)\right)' = \frac12 (36-x^2)^(-1/2) + \frac12 x^2 (36-x^2)^(-3/2)](https://img.qammunity.org/2022/formulas/mathematics/college/l22qdq3qqowrdsz33w5xy541798w8qv9nv.png)
Simplify this a bit by factoring out
:
![\left(\frac12 x(36-x^2)^(-1/2)\right)' = \frac12 (36-x^2)^(-3/2) \left((36-x^2) + x^2\right) = 18 (36-x^2)^(-3/2)](https://img.qammunity.org/2022/formulas/mathematics/college/pc3j7qemidho5xjlkh84bvbb8weg8kjjzx.png)
For the second term, recall that
![\left(\sin^(-1)(x)\right)' = \frac1{√(1-x^2)}](https://img.qammunity.org/2022/formulas/mathematics/college/j8cp0io4fhphn8aga5jv54ktfidgpaj71t.png)
Then by the chain rule,
![\left(18\sin^(-1)\left(\frac x6\right)\right)' = 18 \left(\sin^(-1)\left(\frac x6\right)\right)' \\\\ \left(18\sin^(-1)\left(\frac x6\right)\right)' = (18\left(\frac x6\right)')/(√(1 - \left(\frac x6\right)^2)) \\\\ \left(18\sin^(-1)\left(\frac x6\right)\right)' = \frac{18\left(\frac16\right)}{\sqrt{1 - (x^2)/(36)}} \\\\ \left(18\sin^(-1)\left(\frac x6\right)\right)' = (3)/(\frac16√(36 - x^2)) \\\\ \left(18\sin^(-1)\left(\frac x6\right)\right)' = (18)/(√(36 - x^2)) = 18 (36-x^2)^(-1/2)](https://img.qammunity.org/2022/formulas/mathematics/college/hqxms4c2fauujb0bb4hrn611qvip7ac9te.png)
So we have
![g'(x) = 18 (36-x^2)^(-3/2) + 18 (36-x^2)^(-1/2)](https://img.qammunity.org/2022/formulas/mathematics/college/7o4bv3u4wyjlx5pflhyzj1dnue5rszsd3p.png)
and we can simplify this by factoring out
to end up with
![g'(x) = 18(36-x^2)^(-3/2) \left(1 + (36-x^2)\right) = \boxed{18 (36 - x^2)^(-3/2) (37-x^2)}](https://img.qammunity.org/2022/formulas/mathematics/college/o21gv1100kvuyh9dreb2cv1yjqhmq3wig7.png)